Impact of the size of the lesion in prenatal neural tube defect repair on imaging, neurosurgical and motor outcomes: a retrospective cohort study. (15th June 2020) - Corroenne, R; Zhu, KH; Johnson, E; Johnson, R; Whitehead, WE; Espinoza, J; Castillo, J; Castillo, H; Orman, G; Huisman, TAGM; Mehollin‐Ray, AR; Shamshirsaz, AA; et al.
Abstract : Objectives: (1) To compare brain findings between large and non‐large neural tube defect (NTD); (2) to evaluate the impact of large lesion on the surgical parameters; (3) to study any associations between the size of the lesions and brain findings 6 weeks postoperatively and neurological short‐term outcomes. Design: Retrospective cohort study. Setting: Texas Children's Hospital, between 2011 and 2018. Population: Patients who underwent prenatal NTD repair. Methods: Large lesion was defined when the lesion's surface was >75th centile of our cohorts' lesions. Main outcome measures: Time of referral: ventriculomegaly and anatomical level of the lesion; surgery: duration and need for relaxing incisions. 6 weeks postoperative: hindbrain herniation (HBH) and ventriculomegaly. After delivery: dehiscence, need for hydrocephalus treatment and motor function. Results: A total of 99 patients were included, 25 of whom presented with large lesions. Type of lesion and ventriculomegaly were comparable between individuals with large and non‐large lesions. Individuals with large lesions were associated with increased need for relaxing incisions by 5.4 times (95% CI 1.3–23.2, P = 0.02). Six weeks postoperatively, having a large lesion decreased by ten times the likelihood of having a postoperative reversal of HBH (odds ratio = 0.1, 95% CI 0.1–0.4, P < 0.01). At birth, larger lesions increased the risk for repair dehiscence by 6.1 times (95% CI 1.6–22.5, P < 0.01) and the risk of dehiscence or leakage of cerebrospinal fluid at birth by 5.5 times (95% CI 1.6–18.9, P < 0.01). Conclusion: Prenatal repair of patients with large NTD presents a lower proportion of HBH reversal 6 weeks after the surgery, a higher risk of dehiscence and a higher need for postnatal repair. Tweetable abstract: Evaluation of the size of fetal NTD can predict adverse neurological outcomes after prenatal NTD repair. Tweetable abstract: Evaluation of the size of fetal NTD can predict adverse neurological outcomes after prenatal NTD repair. This article includes Author Insights, a video abstract available at https://vimeo.com/rcog/authorinsights16316